Imperatorin Influences Depressive-like Behaviors: A Preclinical Study on Behavioral and Neurochemical Sex Differences - Kowalczyk, J.; Nakos-Bimpos, M.; Polissidis, A.; Dalla, C; Kokras, N; Skalicka-Woźniak, K.; Budzyńska, B. (Molecules, 2022)
Imperatorin, a naturally derived furanocoumarin, exerts promising neuropharmacological properties. Therefore, it might be applicable in the treatment of brain diseases such as depression. In the present project, we aimed to investigate the sex-dependent effects of imperatorin (1, 5, and 10 mg/kg) on behavior and neurochemistry associated with antidepressant effects. The depressive-like behaviors of male and female Swiss mice were investigated in a forced swim test (FST). Subsequently, High-Performance Liquid Chromatography (HPLC) was used to evaluate the level of serotonin, its metabolite, 5-HIAA, and noradrenaline, in mouse brains. The study revealed that only males responded to imperatorin (1 and 5 mg/kg) treatment and caused an antidepressant effect, such as with respect to depressive-like behaviors, lowering immobility time and increasing immobility latency. The HPLC analysis demonstrated that serotonin levels in the prefrontal cortex of females decreased with the middle dose of imperatorin (5 mg/kg), while in the male prefrontal cortex, the lower dose (1 mg/kg) boosted serotonin levels. There were no evident changes observed with respect to noradrenaline and serotonin metabolite levels in the male hippocampus. To conclude, we propose that imperatorin has antidepressant potential, seemingly only in males, influencing brain serotonin level, but the direct mechanism of action requires further investigation.
Keywords: *Depression/drug therapy/metabolism/physiopathology; *Prefrontal Cortex/metabolism/physiopathology; *Sex Characteristics; Animals; Behavior, Animal/*drug effects; Depression; Female; forced swim test; furanocoumarins; Furocoumarins/pharmacokinetics/*pharmacology; imperatorin; Male; Mice; Noradrenaline; Serotonin; Sex differences